Caffeine, exercise physiology, and time-trial performance: no effect of ADORA2A or CYP1A2 genotypes - Glaister, M.; Chopra, K.; Pereira De Sena, A. L.; Sternbach, C.; Morina, L.; Mavrommatis, Y. (Applied Physiology, Nutrition, and Metabolism, 2021)
The aim of this study was to investigate the influence of ADORA2A and CYP1A2 genotypes on the physiological and ergogenic effects of caffeine. Sixty-six male cyclists were screened for ADORA2A and CYP1A2 genotypes; with 40 taking part subsequently in a randomised, double-blind, placebo-controlled study. Trial 1 was used to establish the oxygen uptake-power output relationship and maximal oxygen uptake. In trials 2 and 3, participants ingested 5 mg·kg-1 of caffeine or placebo 1 h before completing a submaximal incremental cycling test, followed by a time-trial (~30 min). Relative to placebo, caffeine led to a significant reduction in time to complete the time-trial (caffeine: 29.7 ± 1.8 min; placebo: 30.8 ± 2.3 min); but there was no effect of genotype. During submaximal exercise, caffeine reduced mean heart rate by 2.9 ± 3.7 beats·min-1, with effects dissipating as exercise intensity increased. Caffeine also significantly reduced perceived exertion by 0.5 ± 0.8, and increased blood lactate by 0.29 ± 0.42 mmol·L-1, respiratory exchange ratio by 0.013 ± 0.032, and minute ventilation by 3.1 ± 6.8 L·min-1. Nonetheless, there were no supplement × genotype interactions. In conclusion, caffeine influences physiological responses to submaximal exercise and improves time-trial performance irrespective of ADORA2A or CYP1A2 genotypes. Novelty: • Caffeine affects physiological responses at rest and during submaximal exercise independent of ADORA2A or CYP1A2 genotypes. • Variability in the effect of caffeine on time-trial performance is not explained by ADORA2A or CYP1A2 genotypes.